Peran Mediasi Manajemen Laba Diantara Struktur Modal Dan Kinerja Keuangan - Nik Amah; Abd. Rohman Taufiq; Adhelia Oktavian Putri Diyanto (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: This study aims to analyze the effect of capital structure on financial performance mediated by earnings management. Methodology/approach: The research method used is a quantitative approach with secondary data. Samples were taken using purposive sampling to obtain 22 food and beverage subsector companies registered on the IDX during the 2017-2021 period. So, the total observations data is 110. The research analysis techniques using path analysis consist of statistic-t test and sobel test. Findings: The results showed that capital structure has a significant negative effect on financial performance, capital structure has no effect on earnings management, earnings management has no effect on financial performance, and earnings management cannot mediate between capital structure and financial performance. Practical implications: If the company's debt is getting higher, it will cause a real decrease in financial performance. However, agent financing originating from the capital structure can prevent earnings management actions so that these actions do not sufficiently affect financial performance. Originality/value: There are still limited research references regarding capital structure on financial performance mediated by earnings management. This research develops previous research by exploring earnings management with modified Jones measurements in the mediation model.